Application Of The Ma'had Al-Jami'ah Program In Improving The Quality Of Reading The Alquran - Agustina Damanik (Institut Agama Islam Negeri Padangsidimpuan, 2019)
Ma'had Al-Jami'ah is a program that must be followed by students of the State Islamic Institute at Padangsidimpuan. And its become one of the requirements to pass the thesis munaqoshah trial. The existence of Ma'had Al-Jami'ah IAIN Padangsidimpuan is expected to be able to improve the quality of reading the Koran of students. Moreover, IAIN Padangsidimpuan is an Islamic tertiary institution that has considerable to moral responsibility to produce scholars who have competence in the field of reading, memorize and teach the Koran and the formation of morals even better. But even though the Ma'had Al-Jami'ah program has been implemented there are still students who do not yet know about the Qur'an's tahsin properly, as well as some students who have not been able to to have holy attitude and speaks foreign languages (Arabic and English Language) the better one. The purpose of this study is to determine the application of the Ma'had Al-Jami’ah program in improving the quality of reading the Koran well. Knowing the method used by Ma'had Al-jami’ah in improving the quality of reading the Koran. The methods applied by Ma'had Al-Jami’ah are to classificate in some groups according to students' abilities. The grouping starts when students enter the dormitory, Koran reading test held to all students. For students who can read the Koran and know the law of recitation will be separated in another group from students who cannot read the Koran and law of the recitation well. Supporting Rector, Deans, all of IAIN Padangsidimpuan academics community, Student Guardians and Ustadz/Ustadzah is extremely important help this priority program running well